THE INFLUENCE OF COMMUNICATION, WORK ENVIRONMENT, AND DIGITAL LITERACY ON EMPLOYEE PERFORMANCE AT PT. DUA KUDA INDONESIA JAKARTA - Imam Suryono; Endang Anggraini (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This research is driven by the critical role of human resource quality as a strategic asset in navigating global manufacturing competition and the dynamics of Industry 4.0. Fluctuations in employee performance at PT. Dua Kuda Indonesia characterized by punctuality issues and declining output quality necessitate a profound analysis of its determinant factors. Grounded in Human Resource Management as the grand theory, this study examines the influence of communication, work environment, and digital literacy on employee performance. The research methodology used is a quantitative technique combined with an explanatory approach. A questionnaire was used to collect information from 152 respondents selected through purposive sampling at PT. Dua Kuda Indonesia Jakarta. Using SPSS software, data analysis methods included multiple linear regression analysis, classical assumption testing, and hypothesis testing (t-test and f-test). All statement items are valid and reliable, according to research findings from instrument testing, with a Cronbach's Alpha value exceeding 0.60. The normal distribution of the data and the absence of multicollinearity and heteroscedasticity symptoms are confirmed by the findings of traditional assumption tests. Employee performance is positively and significantly influenced by digital literacy, communication, and work environment factors, to some extent. These three factors together significantly enhance performance. The research results confirm that optimal organizational production is determined by a combination of clear work instructions, supportive physical facilities, and technical competence.